Cross-Cultural Adoption of Gamified Attendance Systems: Opportunities and Challenges for Multinational Enterprises - Rahardja, Untung; Andriyansah, Andriyansah; Natalia, Elisa Ananda; Hardini, Marviola; Julianingsih, Dwi (International Journal of Engineering, Science and Information Technology, 2025)
The increasing adoption of gamified systems in workplace settings has garnered significant attention, particularly in multinational enterprises (MNEs) seeking innovative approaches to enhance team member engagement and productivity. Background Gamified attendance systems, integrating game elements such as points, leaderboards, and rewards, present a novel strategy for improving attendance and punctuality across diverse cultural contexts. However, implementing such systems in cross-cultural settings poses unique challenges and opportunities. Objective: This study explores the factors influencing the adoption of gamified attendance systems in MNEs, focusing on cross-cultural adaptability and its implications for organisational performance. Research Method A mixed-methods approach was employed, combining qualitative interviews with HR managers and employees from diverse cultural backgrounds with a quantitative survey targeting 350 employees across 10 MNEs. Data were analysed using thematic analysis and structural equation modelling to identify cultural and organisational determinants of success. Results The findings reveal that cultural dimensions, such as power distance and individualism, significantly impact team member perceptions and engagement with gamified systems. While gamification enhanced attendance rates and morale in low-power-distance cultures, it faced resistance in high-power-distance environments. Additionally, alignment with organisational goals and transparent communication were critical for successful implementation. Conclusion: This study underscores the importance of cultural sensitivity and strategic planning in the cross-cultural adoption of gamified attendance systems. By addressing these factors, MNEs can leverage gamification to foster a more engaged and productive workforce, enhancing global operational efficiency. Future research should explore longitudinal impacts and sector-specific adaptations to optimise implementation outcomes.